2018
DOI: 10.3758/s13415-018-0619-z
|View full text |Cite
|
Sign up to set email alerts
|

Neural evidence for the contribution of holistic processing but not attention allocation to the other-race effect on face memory

Abstract: Multiple mechanisms have been suggested to contribute to the other-race effect on face memory, the phenomenon of better memory performance for own-race than other-race faces. Here, two of these mechanisms, increased attention allocation and greater holistic processing during memory encoding for own-race than other-race faces, were tested in two separate experiments. In these experiments event-related potentials were measured during study (the difference due to memory, Dm) and test phase (old/new effects) to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(59 citation statements)
references
References 56 publications
13
46
0
Order By: Relevance
“…Lucas, Chiao, and Paller (2011) observed more pronounced Dm effects for own-than for other-race faces, which they interpreted to reflect more elaborate processing of own-race faces. Other studies have focused on the different contributions of familiarity and recollection (see Yonelinas, 2002) to own-and other-race face recognition (e.g., Herzmann, Minor, & Adkins, 2017;Herzmann, Minor, & Curran, 2018;Herzmann, Willenbockel, Tanaka, & Curran, 2011). Overall, these studies suggest that successful memory encoding is more effortful for other-compared to own-race faces.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Lucas, Chiao, and Paller (2011) observed more pronounced Dm effects for own-than for other-race faces, which they interpreted to reflect more elaborate processing of own-race faces. Other studies have focused on the different contributions of familiarity and recollection (see Yonelinas, 2002) to own-and other-race face recognition (e.g., Herzmann, Minor, & Adkins, 2017;Herzmann, Minor, & Curran, 2018;Herzmann, Willenbockel, Tanaka, & Curran, 2011). Overall, these studies suggest that successful memory encoding is more effortful for other-compared to own-race faces.…”
Section: Introductionmentioning
confidence: 85%
“…For example, Herzmann et al (2011) found recollection-related Dm effects to be more pronounced for other-relative to own-race faces, which was interpreted to reflect less efficient encoding (see also Herzmann et al, 2017). A more recent study further showed that encoding-related activity contributing to Dm effects is sensitive to task difficulty (Herzmann et al, 2018). The authors observed overall more positive amplitudes during a divided attention compared to a focused attention task during encoding, suggesting the recruitment of additional neural resources when the task is more difficult.…”
Section: Introductionmentioning
confidence: 97%
“…If natural, that is default, memory encoding of own-race faces reflects more elaborate processing, we hypothesized that in the whole-face processing task we would find results identical to the patterns of the Dm and old/new effects for own-race faces from our previous studies (Herzmann et al, 2011(Herzmann et al, , 2017(Herzmann et al, , 2018. For own-race faces in the single-feature processing task, we expected to see patterns of the Dm that resembled those of other-race faces in the single-feature processing task because task instructions would prevent the naturally occurring more elaborate processing (Stahl et al, 2010).…”
Section: Introductionmentioning
confidence: 82%
“…Old/new effects contrast brain activation for old as compared to new items and have been found to show specific ERP components for familiarity, the FN400, and recollection, the parietal old/new effect (Curran, 2000;Rugg & Curran, 2007). The FN400 has been inconsistently observed in face recognition studies (Curran & Hancock, 2007;Herzmann et al, 2011Herzmann et al, , 2017Herzmann et al, , 2018Yovel & Paller, 2004). We therefore focus our review on the parietal old/new effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation